Attitudes of Lebanese adults regarding COVID-19 vaccination - Carina Kasrine Al Halabi; Sahar Obeid; Hala Sacre; Marwan Akel; Rabih Hallit; Pascale Salameh; Souheil Hallit (BMC, 2021)
Abstract Background COVID-19 was first detected in Lebanon on February 21, 2020; it reached its peak in January 2021, with a total number of 418,448 confirmed cases and 5380 deaths (until March 15, 2021). Gaining insight into factors regarding willingness or refusal for vaccination might guide our goals in raising the awareness and target efforts to increase acceptance of the COVID-19 vaccine and maximize the uptake. Therefore, this study aims to assess the intent to receive the COVID-19 vaccine among Lebanese adults and the factors associated with vaccine refusal. Methods We conducted a cross-sectional study during November-December 2020 among Lebanese adults from all Lebanese regions using a survey tool with closed-ended questions that included sociodemographic data and questions about vaccine hesitancy, knowledge, attitude, practice, and fear of COVID-19. We used the snowball technique to collect the data because of the COVID-19 imposed lockdown. Results Of the 579 participants, 21.4% were willing to receive the vaccine, 40.9% refused, and the remainder were unsure of their response. More vaccine hesitancy (adjusted odds ratio (aOR) = 1.06; 95% CI 1.03-1.09) was significantly associated with more odds of disagreeing/ strongly disagreeing on receiving the COVID-19 vaccine compared to being neutral. More vaccine hesitancy (aOR = 0.95; 95% CI 0.91-0.99), female gender compared to males (aOR = 0.53; 95% CI 0.32-0.87), and being married compared to single (aOR = 0.53; 95% CI 0.29-0.98) were significantly associated with lower odds of agreeing/strongly agreeing on receiving the COVID-19 vaccine compared to being neutral. Conclusion Overall, our findings revealed a high percentage of people (40%) who strongly disagreed with receiving the vaccine, mainly females, married participants, and those who have a general vaccine hesitancy. Moreover, no significant association was found with knowledge, attitude, or prevention practice regarding COVID-19. Targeted efforts are necessary to increase acceptance of a COVID-19 vaccine among the Lebanese population to control the COVID-19 pandemic. Further studies with a larger sample size are warranted to validate our results and provide better insights into the underlying reasons for refusing vaccination.